Effect of etanercept and gold nanoparticles on the expression of tnfr2+ regulatory t cells and cd103+ dendritic cells in peripheral blood mononuclear cells of asthma patients - Ahmad, Suhana (2020)
Immune tolerance by regulatory T cells (Tregs) is one of the various mechanisms, which is employ to maintain homeostasis and protect the host against various environmental stimuli. Recently, a subset of Tregs expressing tumor necrosis factor receptor 2 (TNFR2+ Tregs) is identified as a more suppressive and proliferative cell population and its regulation is reported to be impaired in respiratory dysfunction condition such as asthma. Gold nanoparticles (AuNPs), a highly potential tool in immunotherapies, are shown to be protective against key features of asthma. Hence, the current study would like to elucidate the effects of AuNPs on the expression of TNFR2+ Tregs, as well as on CD103+ dendritic cells (DCs), which have been shown to induce Tregs in asthmatic individuals and whether a TNFR2 agonist, etanercept, can modulate the effects of AuNPs. A five-color flow cytometry assay was used to determine the expression of cell population of interest in asthmatic and non-asthmatic controls (n=6) and traditional ELISA assay to determine the level of TNF-α and IL-10. Stimulation of peripheral blood mononuclear cells (PBMCs) of asthmatic individuals with AuNPs for 24 hours does not induce significant effects on the cell population of interest. Meanwhile, etanercept as anti-TNF is shown to significantly decrease TNFR2+ Tregs (p = 0.0210) and T effector cells TNFR2+ (Teff) (p = < 0.0001) with an increased pattern of Foxp3+ Tregs only. Surprisingly, etanercept is shown to significantly increased the level of TNF-α, question the principal mechanism of etanercept as TNF antagonist. Correlation analysis in the current study demonstrated inverse association of CD103+ DCs with Tregs including TNFR2+ Tregs (r = - 0.6853, p = 0.0170), indicates to the independency of this subset of DCs in the regulation of immune homeostasis, particularly in asthma. Results indicated to the potential of AuNPs as potential formulation carrier for immunotherapies due to its capability to be effectively uptake by antigen-presenting cells such as DCs without inducing immune response.